2019
DOI: 10.1021/acs.macromol.9b01559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Solid-State Properties of PolyC3 (Co)polymers Containing (CH2–CH2–C(COOR)2) Repeat Units with Densely Packed Fluorocarbon Lateral Chains

Abstract: The synthesis and structural characterization of linear PolyC 3 polymers containing trimethylene-1,1-dicarboxylate structural repeat units, with C 6 F 13 and C 8 F 17 fluorinated side chains is described for the first time, and their properties compared with the traditional polyvinyl structures that display the fluorinated chain on every second rather than on every third carbon alongside the backbone. Homopolymers as well as statistical and block copolymers with npropyl and/or allyl trimethylene-1,1-dicarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Poly(trimethylene-1,1-dicarboxylate lithium) was synthesized by ring-opening polymerisation followed by hydrolysis of ester and ion exchange reaction as described in previous publications [10,14]. Polyacid was obtained from lithium salt using an ion exchange column loaded with the cation exchange resin Amberlite IR 120 Na.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poly(trimethylene-1,1-dicarboxylate lithium) was synthesized by ring-opening polymerisation followed by hydrolysis of ester and ion exchange reaction as described in previous publications [10,14]. Polyacid was obtained from lithium salt using an ion exchange column loaded with the cation exchange resin Amberlite IR 120 Na.…”
Section: Methodsmentioning
confidence: 99%
“…The product yield was approximately 40%. Sodium and potassium salts were obtained by addition of excess of respective hydroxide [14]. In further discussion polyacid, lithium, sodium and potassium salts ate noted as H2, Li2, Na2 and K2, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such semi-rigid amphiphilic compounds, known as calamitics, are known to form layered, cylindrical, or cubic superstructures as a function of molecular shape, temperature, humidity, etc. [16][17][18]. For example, Berrod et al [19] suggested original perfluorosulfonic acid molecules that can reproduce the phase-separated morphology of PFSA ionomer membranes used as electrolytes in fuel cells.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high ionization potential and low polarizability of fluorine, fluorinated compounds are known as the most effective materials to provide the ultralow surface free energy required for many applications, such as water and oil repellencies, anticorrosion, antismudge, drag reduction, ice-releasing, and fouling resistance. Among the fluorinated materials, fluorinated polymers (or fluoropolymers) have been developed as an important branch since the discovery of poly­(tetrafluoroethylene) (PTFE) by Plunkett in 1938. , Fluorinated polymers can be divided into two groups: (I) those where the fluorinated carbons are located in the polymer backbone and (II) those containing fluorinated dangling side groups. In recent years, group (II) has attracted increasing research interest due to the high density of trifluoromethyl (−CF 3 ) terminal groups, tunable linkers between the dangling group and the backbone, and the improved solubility and processability compared with that of group (I). In particular, the polymers of perfluoroalkyl-substituted acrylates (PFAs) or methacrylates (PFMAs) maintain both the special surface property of fluoropolymers and the good film-forming characteristic of poly­(meth)­acrylates. , …”
Section: Introductionmentioning
confidence: 99%